CO2 fluxes from drained tropical peatland used for oil palm plantation in relation to peat characteristics and crop age after planting - EVI GUSMAYANTI; GUSTI Z ANSHARI; MUHAMMAD PRAMULYA; AGUS RULIYANSYAH (Biodiversitas Journal of Biological Diversity, 2019)
Large expansion of oil palm plantation on peatland has changed its important role for carbon sink into a carbon source.  Conversion of peat swamp forest with high carbon density into a monoculture of oil palm has released the significant amount of carbon into atmosphere either carbon previously stored in forest biomass or carbon stored in peat organic matter.  Drainage canal to artificially lower groundwater level as a prerequisite of oil palm cultivation provides the favorable condition for soil microbes activities in decomposing peat organic matter resulted in CO2 flux increase.  The fluctuation of groundwater level and variation of environmental factors near the peat surface may regulate the rate of CO2 released from the soil.  We aimed to measure CO2 fluxes from two sites of oil palm plantation with different peat characteristics and analyzed the correlation with groundwater level, soil temperature, air temperature,  gravimetric water content, peat pH, oxidative reductive potential, and crop age.  The measurement has been conducted from September 2016 to April 2017 in West Kalimantan, Indonesia by using portable infrared gas analyzer EGM 4.  In addition to soil sampling at the same time as the gas measurement, we collected soil samples for some peat characteristics analysis consist of bulk density, particle density, porosity, soil organic matter, ash content, carbon, and nitrogen content prior to CO2 flux measurement.  Our result shows that the difference of peat chemical characteristics between two sites has resulted in different CO2 flux.  Oil palm ages seemed to affect CO2 flux by regulating microclimatic condition around crop canopy.  Another finding is the insignificant relationship between CO2 fluxes and groundwater level unless the groundwater level reached more than 50 cm from the peat surface.  It implies that maintaining groundwater level-up to 50 cm resulting in similar CO2 flux.